Symbolic effects of the implantation of the indigenous health home: a historical study. - Amorim, Raphael Florindo (2021)
Aim: To describe the symbolic effects of the implementation of the indigenous health home in the field of health in the period from 1973 to 1983 in Boa Vista, Roraima, Brazil. Methods: This was a historical study with a microhistory approach guided by a documentary analysis; the theorization of the results was guided by the concepts of the sociologist Pierre Bourdieu. Results: The documentary corpus was represented by four imagery records. The images were analyzed in order to produce reflections on the symbolic effects of the implantation of the indigenous health home. Conclusion: The indigenous health home in Boa Vista-RR emerges as a backdrop in this developmental scenario; it represents a symbolic currency of exchange between the government and the indigenous people who suffered from the entry of diseases in their communities through the direct action of the migratory process and the mining in their lands.